The Influence of Locus of Control and Lifestyle on Financial Behavior in Generation Z (Animation Department Students of SMK Negeri 5 Malang) - Nur Ida Iriani; Imam Hidayat; Flea Awang Nugraha (International Journal of Management and Business, 2026)
This study aims to analyze the Influence of Locus of Control and Lifestyle on Financial Behavior in Generation Z (Animation Department Students of SMK Negeri 5 Malang). This study uses a quantitative method with a population of 182 Animation Department students at SMK Negeri 5 Malang. The sampling technique used in this study was purposive sampling and data collection using a questionnaire with a sample of 65 respondents. Multiple linear analysis techniques using t-test and f-test are the test tools used. The data was processed using SPSS 26 software. The results of this study are: (1) there is a positive and significant influence of Locus of Control on Financial Behavior in Generation Z (2) there is a positive and significant influence of Lifestyle on Financial Behavior in Generation Z (3) there is an influence of Locus of Control and Lifestyle on Financial Behavior in Generation Z. This means that Locus of Control and Lifestyle will simultaneously influence Financial Behavior in Generation Z (Animation Department Students of SMK Negeri 5 Malang).